IDEOLOGI, AKTIVITAS, DAN PERAN KOMUNITAS SENI BELANAK DALAM PERKEMBANGAN SENI RUPA SUMATRA BARAT - Muslimaniati Muslimaniati; Erfahmi Erfahmi (Serupa The Journal of Art Education, 2021)
The objectives of this research are (1) to describe the background and ideology of the Belanak Art Community, (2) to describe the activities of Belanak Art Community during its existence, and (3) to describe the role of Belanak Art Community in the development of West Sumatra’s art. This research uses descriptive method with a qualitative aoncoming. The results showed that with the Belanak ideology this community was born because of anxiety and the need for a better art climate, activities carried out such as exhibitions, discussions, etc., and played a role in the educational position and the art field of West Sumatra.Kata Kunci : Ideologi, Aktivitas, Peran, Komunitas Seni Belanak, Seni Rupa Sumatra Barat